PENGARUH MODEL PEMBELAJARAN TEAM ASISSTED INDIVIDUALIZATION TERHADAP HASIL BELAJAR KOGNITIF PADA SISWA KELAS VIII SMP - Zulfriansyah, Argo; Mering, Aloysius; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research has purpose to know the influence of Project Cooperative Learning Model of Team Asissted Individualization (TAI) to the Cognitive Learning Outcomes of Music Art. The subject of research are eight grade students of SMPN 03 Sungai Raya. This research uses experimental method with Pre-Experimental Design and Quantitative approach. The design used in this research is One-group Pretest-Posttest Design. The sample in this study is class VIII C which amounts to 24 students, determined by simple way (simple random sampling). Technique used in data collection is the measurement. The data collection tool used is a written test of objective form. Based on data analysis, the result of the average of pre-test of student equal to 58,75 and average result of student's post-test equal to 74,75. After t test, tcount is obtained 12,451, ttable with dk = 24-1 = 23, and 5% significant level is 1,694, thus tcount â‰¥ ttable or 12,451 â‰¥ 1,694 which means there is significant influence on applying cooperative learning model team asiisted individualization. Based on t test result, it can be concluded that there is influence of team assisted individualization model to cognitive learning result of music art of class VIII C students at SMP N 03 Sungai Raya.Keywords: cooperative learning model of team assisted individualization, cognitive learning outcomes.